2007
DOI: 10.1021/cb7000044
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for High-Affinity Peptide Inhibition of Human Pin1

Abstract: Human Pin1 is a key regulator of cell-cycle progression and plays growth-promoting roles in human cancers. High-affinity inhibitors of Pin1 may provide a unique opportunity for disrupting oncogenic pathways. Here we report two high-resolution X-ray crystal structures of human Pin1 bound to non-natural peptide inhibitors. The structures of the bound high-affinity peptides identify a type-I beta-turn conformation for Pin1 prolyl peptide isomerase domain-peptide binding and an extensive molecular interface for hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
183
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(199 citation statements)
references
References 58 publications
11
183
0
Order By: Relevance
“…Different research groups are currently developing Pin1 small-molecule inhibitors, whose efficacy in anticancer therapy should be tested in vivo. [32][33][34] Furthermore, we have found that the other two members of the pocket protein family, namely p130/pRb2 and p107, are substrates of Pin1. As in T98G cells the Pin1 and pRb interaction plays a major role in the G1/S cell cycle control, it would be interesting to analyze Pin1, pRb2/p130, and p107 in other cancer cells or other physiological processes.…”
Section: Discussionmentioning
confidence: 92%
“…Different research groups are currently developing Pin1 small-molecule inhibitors, whose efficacy in anticancer therapy should be tested in vivo. [32][33][34] Furthermore, we have found that the other two members of the pocket protein family, namely p130/pRb2 and p107, are substrates of Pin1. As in T98G cells the Pin1 and pRb interaction plays a major role in the G1/S cell cycle control, it would be interesting to analyze Pin1, pRb2/p130, and p107 in other cancer cells or other physiological processes.…”
Section: Discussionmentioning
confidence: 92%
“…More specific Pin1 inhibitors with less side effects are required. Promising candidates are the substituted aryl 1-indanyl ketones (53) and a series of specific D-phospho-Thr-containing peptides (54,55). Such inhibitors might not only be useful in studying the functional relevance of Pin1 in vivo; they could also provide the therapeutic basis to treat pathological conditions in which Pin1 is aberrantly upregulated, such as cancer (8).…”
Section: Discussionmentioning
confidence: 99%
“…These inhibitors contained non-proteogenic amino acids and blocked cell cycle progression in HeLa cells in a dose-dependent manner. In addition, high resolution crystal structures of the D-and L-forms of two of these pentameric inhibitors have been published (Zhang et al, 2007). In the structure of the L-peptide complex the pThr-Pip (piperidine-2-carboxylic acid) carbonyl group faces away from the side chains of Arg 68 , Gln 131 and Ser 154 , resulting in an ω bond angle close to the cis conformation, whereas in the D-peptide-complex the carbonyl moiety forms a hydrogen bond with the Ser 154 hydroxyl group.…”
Section: Peptidic Inhibitors and Substrate Analogsmentioning
confidence: 99%